Disrupting ELL Teacher Candidates' Identities: Indigenizing Teacher Education in One Study Abroad Program. Issue 3 (September 2016) - Kasun, G. Sue; Saavedra, Cinthya M.
Abstract : In this article, the researchers describe and theorize the challenges and promises of exposing preservice teachers' identities to indigenous, critical second language teaching experiences in one study abroad program in Mexico. The eight teacher candidates who participated in this 4‐week program were predominantly white, like the majority of teachers of English language learners in the United States today. By analyzing teacher candidates' self‐assessments, course work samples, class discussions, focus group sessions, and ethnographic field notes, the researchers found three main themes of identity shifts: becoming socially aware, becoming empaths, and becoming creators of loving classroom spaces. These tentative changes appear to be the result of a carefully crafted curriculum, including the extracurricular activities organized in concert with the social justice language institute with whom the researchers partnered. At the same time, the teacher candidates' identities worked in tensions with former identities already created, such as being excellent "classroom managers." The researchers show these tensions and realistic hopes regarding the teacher candidates. This program—and other alternatives to preparing preservice teachers attempting to work with culturally and linguistically minoritized communities—can serve as examples of beginning efforts to decolonize curricula. This critical approach to teacher preparation creates cracks between worlds (Anzaldúa, 2002) that allow preservice teachers to rethink their identities as second language teachers in local and global contexts.